Macrofungi in Mediterranean maquis along seashore and altitudinal transects - Pecoraro, Lorenzo; Angelini, Paola; Arcangeli, Andrea; Bistocchi, Giancarlo; Gargano, Maria Letizia; Rosa, Alfonso La; Lunghini, Dario; Polemis, Elias; Rubini, Andrea; Saitta, Alessandro; Venanzoni, Roberto; Zervakis, Georgios I (Plant Biosystems - An International Journal Dealing with all Aspects of Plant Biology, 2014)
In semiarid Mediterranean environments, fungal activity is fundamental for buffering biotic and abiotic stress to the plant and for sustaining a vegetation cover. Despite the important role that fungi play in habitats stability, mycological data from Mediterranean ecosystems are scarce and fragmentary. We investigated fungal diversity in several areas characterized by Mediterranean maquis, from continental Italy, Sicily and Greece in order to contribute to the analysis of distribution, ecology and diversity of macrofungi in evergreen sclerophyllous shrublands at different elevation and distance from the seashore across the Mediterranean Basin. Several fungal taxa that are remarkable due to their ecology, rarity and limited geographical distribution were recovered. Among them, the ectomycorrhizal species Amanita dunensis and A. valens were recorded for the first time in Italy. The wood-inhabiting macrofungi, Aleurodiscus dextrinoideocerussatus, Peniophorella tsugae, Perenniporia meridionalis, Phanerochaete martelliana, Vararia ochroleuca and six Peniophora species were reported for the first time in Greece. Some species, such as Gloeodontia columbiensis, Ceriporia aurantiocarnescens, Peniophora pithya and P. tamaricicola were collected on new substrates. For the two rare basidiomycetes Amanita eliae and Battarrea phalloides, molecular identification and phylogenetic analysis gave valuable information on their relationship with similar taxa.
doi: 10.1080/11263504.2013.877535
Keywords: ectomycorrhizal species; macromycetes; Mediterranean ecosystems; molecular analysis; saprotrophs; wood-inhabiting fungi

Crepidotus eucalyptinus and Simocybe haustellaris: two uncommon species found in Central Spain - Bandala, Victor M; Montoya, Leticia; Esteve-Raventos, Fernando (MYCOTAXON, 2008)
Crepidotus eucalyptinus and Simocybe haustellaris were collected together from a Quercus ilex subsp. ballota forest in Central Spain (Guadalajara Province). Collections of both species are described and their taxonomically distinctive microscopic characters are illustrated. The superficial similarity between these two brown-spored taxa is discussed as well as the taxonomic status of the former within Crepidotus and the close affinity of the species with Naucoria decolorata from Morocco and Spain.
Keywords: Crepidotaceae; taxonomy; wood-inhabiting fungi